The Effect of Warm-Up Games on Motivation to Learn Football Among Students at Muaro Jambi State Junior High School 1 (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of small games during warm-up activities on the learning motivation of eighth-grade students in football lessons at SMP Negeri 1 Muaro Jambi. The research method used was an experimental approach with a pretest–posttest design. Research instruments included motivation questionnaires, observation, and documentation. The small games applied consisted of Sen the Ball, Rescue Ball, Optimus Race, Cat-and-Mouse, Invasion Game, Agility and Teamwork, Group Dribbling, and Ball Relay. The results of the study showed a significant increase in students’ learning motivation after the treatment. The average motivation score increased from 120.23 (pretest) to 167.23 (posttest). The t-test result indicated that the calculated t value was higher than the table value, thus confirming the research hypothesis. It can be concluded that small games in warm-up activities have a positive and significant effect on enhancing students’ motivation in learning football at SMP Negeri 1 Muaro Jambi, with an improvement of 28.8%.